JOE DOUGLAS: FROM TRAUMA TO LEGACY – THE POWER OF MENTORSHIP, VISION, AND ENTREPRENEURIAL EDUCATION IN SHAPING BUSINESS MINDSETS - da Silva, João Douglas (Revista Sistemática, 2023)
This article explores the transformative journey of Joe Douglas, a Brazilian immigrant entrepreneur in the United States, emphasizing the critical roles of mentorship, visionary leadership, and entrepreneurial education in shaping resilient business mindsets. Drawing on theoretical frameworks from developmental mentoring, transformational leadership, and experiential learning, the study highlights how personal trauma can be reframed into entrepreneurial strength. Furthermore, it discusses the unique challenges faced by immigrant entrepreneurs and the importance of psychological capital and social networks in overcoming systemic barriers. Douglas’s integrated approach offers a replicable model that underscores human development as foundational to sustainable business success.